2022
DOI: 10.3389/fcimb.2021.810398
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Mapping, and Genetic Diversity of Novel Conserved Cross-Species Epitopes of RhopH2 in Plasmodium knowlesi With Plasmodium vivax

Abstract: Malaria is a major public health concern, and any tangible intervention during the pre-elimination phase can result in a significant reduction in infection rates. Recent studies have reported that antigens producing cross-protective immunity can play an important role as vaccines and halt malaria transmission in different endemic regions. In this study, we studied the genetic diversity, natural selection, and discovered novel conserved epitopes of a high molecular weight rhoptry protein 2 (RhopH2) in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…It assumes that the folded protein structure puts minimum strain on side-chain conformations, favoring low-energy positions during folding [ 48 ]. Since P. knowlesi and P. vivax are phylogenetically close and several studies have shown the importance of conserved cross-species vaccine candidates [ 11 , 49 , 50 ]. Therefore, in addition to identifying epitopes in P. knowlesi, this study examined the likelihood of epitope conservation with P. vivax .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It assumes that the folded protein structure puts minimum strain on side-chain conformations, favoring low-energy positions during folding [ 48 ]. Since P. knowlesi and P. vivax are phylogenetically close and several studies have shown the importance of conserved cross-species vaccine candidates [ 11 , 49 , 50 ]. Therefore, in addition to identifying epitopes in P. knowlesi, this study examined the likelihood of epitope conservation with P. vivax .…”
Section: Methodsmentioning
confidence: 99%
“…In many countries outside of sub-Saharan Africa, P. vivax is the most prevalent species [ 1 ]. The simian malaria parasite P. knowlesi has been discovered to cause human infection, as reported from several Southeast Asian countries, particularly in Malaysian Borneo [ 4 , 9 , 10 , 11 , 12 , 13 , 14 ]. Due to its increasing incidence in recent years, P. knowlesi malaria has become a significant public health issue in the region [ 4 , 9 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic, antigenic diversity and the ability to evade host immune responses are major obstacles hindering the development of effective anti-malaria vaccines. Many studies have focused on conserved regions or epitopes common between vast ranges of plasmodium strains 6 . P. falciparum glutamic acid-rich protein (PfGARP) is an 80 kDa antigen expressed on the surface of infected erythrocytes with P. falciparum 7 .…”
Section: Introductionmentioning
confidence: 99%